(untitled) (Web of Teachers: Inderscience Research, 2024)
This article reveals the meaning of such concepts as "intercultural competence", "pedagogical technology", "game learning technologies", "project learning technology"; traditional and innovative pedagogical technologies for the development of intercultural competence, identified by well-known both foreign and domestic researchers, are given as an example; describes the most effective, from our point of view, technologies for the development of intercultural competence, namely: the technologies of game and project-based learning used in foreign language lessons at the stage of primary general education.